2020
DOI: 10.1108/pr-01-2019-0026
|View full text |Cite
|
Sign up to set email alerts
|

Chasing productivity demands, worker well-being, and firm performance

Abstract: PurposeThis study aims to examine the impact of chasing productivity demands on worker well-being and firm performance in manufacturing firms in Malaysia. Flexible work arrangements and human resources support are used as moderators to mitigate the adverse impacts associated with chasing productivity demands.Design/methodology/approachData were collected from 213 workers from manufacturing firms through a survey questionnaire utilizing structural equation modeling.FindingsThe findings of the study show that fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 81 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…, 2020). We also recommend organizations to show a supportive reaction to their employees and offer adequate work resources when a crisis occurs (Fiksenbaum, 2014; Wahab and Tatoglu, 2020). Specifically, supervisor support plays a significant role in helping employees achieve improved WLB (Blahopoulou, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2020). We also recommend organizations to show a supportive reaction to their employees and offer adequate work resources when a crisis occurs (Fiksenbaum, 2014; Wahab and Tatoglu, 2020). Specifically, supervisor support plays a significant role in helping employees achieve improved WLB (Blahopoulou, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These trainings would help employees mitigate conflicts of resource allocation, which is likely to increase their overall performance and a more balanced response to life demands (Grawitch et al, 2010;Obrenovic et al, 2020). We also recommend organizations to show a supportive reaction to their employees and offer adequate work resources when a crisis occurs (Fiksenbaum, 2014;Wahab and Tatoglu, 2020). Specifically, supervisor support plays a significant role in helping employees achieve improved WLB (Blahopoulou, 2015).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Our interest is in the extent to which the views of GRs and CAs align or diverge, expanding the literature by manifesting the collaborative‐competitive nature of relationships between career actors, as well as offering practical implications for future collaborative agendas. These insights can facilitate organizations to optimize their use of technology for talent management and the associated sustainable competitive advantage (Ab Wahab & Ekrem, 2020; Illes et al, 2010; Mulder, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The demand for remote working opportunities has seen digital nomadism become increasingly institutionalized and professionalized (Aroles et al, 2020; Gazit et al, 2021). Managing these challenges is crucial since talent management determines competitive advantage and organizational sustainability (Ab Wahab & Ekrem, 2020; Illes et al, 2010). The widening gap between the technological‐human intersection within and between organizations, and its effects on talent management and careers (Kim et al, 2022), therefore, emphasize the need for research to explore these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Chung and van der Lippe (2020) found that FWA is conducive to balancing family and work relationships. The third research approach takes the organizational perspective, examining organizational antecedents (e.g., organizational culture characteristics) ( Lyness et al, 2012 ; Masuda et al, 2012 ), and organizational outcomes (e.g., performance or competitiveness) ( Stavrou, 2005 ; Wahab and Tatoglu, 2020 ). However, the results of these studies indicate that FWA as a work arrangement design at the organizational level is complex and difficult to analyze.…”
Section: Introductionmentioning
confidence: 99%